Application of fuzzy evaluation technique and grey clustering method for water quality assessment of the coastal and estuaries of selected rivers in Sarawak - Ebenezer Aquisman, Asare; Zaini, Assim; Rafeah, Wahi; Rajuna, Tahir; Eric Kwabena, Droepenu (BioMed Central Ltd, 2021)
Background: Estuarine and marine water quality has remarkable importance because these water resources are used for multiple reasons for instance: transportation, tourism, recreation, and other human or economic ways to use water. The objective of the study was to assess the water quality of the coastal and estuaries of the Rambungan, Sibu, Salak, and Santubong rivers in Sarawak, Malaysia. Water samples were collected from 10 locations and analyzed by employing standard techniques. A fuzzy comprehensive evaluation, grey clustering evaluation methods, Thailand Marine Water Classifcation System, and the Malaysian Marine Water Quality Index (MMWQI) and its classifcation system were applied to compute the index of each water quality parameter. Results: The results showed that all the analyzed water quality parameters were within the allowable threshold lev‑ els. The results obtained by the application of fuzzy comprehensive evaluation and grey clustering evaluation meth‑ ods proved that the coastal and the estuaries waters were clean with exception of coastal location CZ9 and the estu‑ ary of Salak river which showed slight pollution. Based on the Malaysian Marine Water Quality Index, it was observed that all the locations were in the classifcation group of moderate (i.e. 50–79%). This suggests that the estuaries of selected rivers can be used for natural resource conservation, while the coastal regions are good for fsh farming. Conclusion: It can be deduced that the suggested techniques were workable and logical. The method developed and the information in this study can serve as a reference and decision support for scientists and policymakers of concern